The Potential of Sri Lankan Teacher in Managing Online Classroom - Wickramanayake, R.; Kumari, H.M.L. (International Journal on Integrated Education, 2022)
The purpose of this empirical research was to examine how the Sri Lankan teachers manage their online classrooms. Three research questions were used to guide the study to a rational conclusion. Accordingly, the study was focused to get an insight idea on how teachers manage physical and digital resources and human resource in their online classrooms and the problems that the teachers face during their online teaching. Sequential mixed methodology was followed for the data triangulation which quantitative data was collected and analyzed first, followed by qualitative data. A survey was administered for the first phase while semi-structured interviews and online classroom observations were implemented for the second phase to obtain data from 205 teachers in 10 selected 1AB and 1C schools. Quantitative data was analyzed by descriptive and inferential statistical methods using tables, graphs and percentages while qualitative data was analyzed using thematic analysis. The study revealed that 55.5% of teachers effectively manage physical and digital resources in online classrooms and 52.5% manage human resource. The research further revealed that many teachers had problems in managing online classrooms due to low student participation and non-continuity of internet signals. Also, the univariate analysis conducted through the research revealed that the type of school affects the physical and digital resources and human resource management in the online classrooms and it does not vary according to the education zone. Accordingly, it was unveiled that the school has a significant impact on the emergence of the teacher's management ability.
Keywords: Classroom Management; Online Classroom Management; Online Education; Digital Literacy